Disparities in Peripheral Artery Disease-related Mortality in Chronic Inflammatory Disease in the United States from 1999 to 2020 - Olson, April; Pham, Hoang Nhat; Ibrahim, Ramzi; Salih, Mohammed; Singh, Amitoj; Mamas, Mamas A. (Current Cardiology Reviews, 2025)
IntroductionPeripheral arterial disease (PAD) is a marker of significant atherosclerotic cardiovascular disease and is associated with greater healthcare burden and worse prognosis in individuals with chronic inflammatory disease (CID). We aimed to investigate temporal trends and disparities of PAD-related mortality in populations with CID from 1999-2020 across six common CIDs (i.e., chronic viral hepatitis, human immunodeficiency virus, inflammatory bowel disease, psoriasis, rheumatoid arthritis, and systemic lupus erythematosus).MethodsUnited States (US) PAD and CID-related mortality and demographic data from 1999-2020 were extracted from the CDC database through the multiple-cause-of-death files. Age-adjusted mortality rates (AAMR) per 1,000,000 and 95% confidence intervals were standardized to the 2000 US population. The mortality trends were analyzed using Joinpoint Regression.ResultsA total of 22,175 PAD-related deaths were recorded in the population with CID between 1999 and 2020. Mortality remained stable during the 22-year period (AAPC -0.04%, p=0.95) with a cumulative AAMR of 4.64. Mortality was highest in rural counties (AAMR 5.27), and among non-Hispanic Black populations (AAMR 7.06). Among the CID subtypes, PAD mortality was highest in populations with RA (AAMR 2.48) and lowest in populations with psoriasis (AAMR 0.11).ConclusionOur findings highlight the disparities of PAD mortality in patients with CID, with the Black population and rural communities disproportionately affected. Further investigation with individual-level data is warranted to identify the contributing factors for the observed disparities.
Keywords: chronic inflammatory disease